Cooperative polariton dynamics in feedback-coupled cavities - Bimu Yao; Y. S. Gui; J. W. Rao; S. Kaur; X. S. Chen; W. Lu; Y. Xiao; H. Guo; K. -P. Marzlin; C. -M. Hu (Nature Communications, 2017)
Rabi oscillations of magnons typically do not have few photon control of single spin quantum systems. Here, the authors use a feedback cavity architecture to increase magnon-photon cooperativity, enabling increased control of light-matter interactions in magnonic systems via cooperative polariton dynamics.